Levels and correlates of physical activity and screen time among early years children (2–5 years): Cross‐cultural comparisons between Canadian and South Korean data. (7th February 2021) - Lee, Eun‐Young; Song, Yoon‐Kyung; Hunter, Stephen; Jeon, Justin; Kuzik, Nicholas; Predy, Madison; Carson, Valerie
Abstract: Background: Cross‐cultural research can provide insight into whether levels and correlates of movement behaviours among early years children vary across different cultural contexts. This study (1) compared children's physical activity (PA) and screen time (ST) and parental and environmental correlates of PA and ST between samples of Canadian and South Korean (Korean thereafter) early years children (2–5 years) and (2) investigated parental and environmental correlates of PA and ST and whether country moderates the relationships. Methods: Cross‐sectional data from 121 Canadian children (3.4 years; 49.6% girls) and 101 Korean children (3.4 years; 54.9% girls) who participated in the Parents' Role in Establishing healthy Physical activity and Sedentary behaviour habits (PREPS) study were used. Demographic information, children's PA, ST, PA‐ or ST‐specific parental cognitions and behaviours, and home and neighbourhood environments were measured using a proxy‐reported questionnaire. Two‐tailed independent samples T test or Mann Whitney U test, chi‐square tests, linear regression and moderation analyses were performed. Results: Canadian children spent more time in non‐organized PA compared to Korean children (111 vs. 63 min/day), whereas time spent in organized PA was higher in Korean children than Canadian children (25 vs. 9 min/day). Canadian children had more ST than Korean children (159 vs. 110 min/day). Similarly, Canadian parents reported higher screen (142 vs. 116 min/day) and sitting time (317 vs. 286 min/day) than Korean parents. Though children's behaviours, as well as parental cognitions and behaviours, varied between the two samples, similar correlates of children's PA and ST were observed. The relationship between presence of electronics in children's bedrooms and children's ST was moderated by country, with Canadian children showing a stronger relationship than Korean children. Conclusions: Supporting parents to adopt cognitions and behaviours that are conducive to healthy PA and ST patterns of their own and their early years children may be important for both Canada and Korea.